SARS-CoV-2 vaccine hesitancy in patients with heart failure: relationship with patient characteristics and pre-pandemic quality of life – a cohort study - Sawczak, Filip; Kukfisz, Agata; Cierzniak, Maria; Szubarga, Alicja; Soloch, Aleksandra; Balewska, Anita; Szczechla, Magdalena; Krysztofiak, Helena; Przytarska , Katarzyna; Dudek, Magdalena; Uchmanowicz, Izabella; Straburzyńska-Migaj , Ewa; et al. (Journal of Medical Science, 2023)
Heart failure (HF) patients are vulnerable to a complicated course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. This research analysed the relationship between the decision not to be immunised against SARS-CoV-2, clinical and epidemiological factors, and the pre-pandemic health-related quality of life (HRQoL) of HF patients. Before the onset of the SARS-CoV-2 pandemic, hospitalised HF patients were enrolled as a prospective cohort and interviewed using the World Health Organization's Quality of Life Brief Version questionnaire. On October 30, 2021, the immunisation status was verified. The association of vaccination hesitancy with epidemiological and clinical parameters and pre-pandemic questionnaire results was tested. Subsequently, independence from confounding factors such as age, sex, the New York Heart Association (NYHA) scale, and left ventricular ejection fraction (LVEF) was analyzed. Among the 136 included patients, 77.9% were vaccinated. Unvaccinated patients were younger (51.2±13.2 vs 56.6±10.3; p = 0.018) and more frequently had non-ischaemic aetiology of HF (73.3% vs 46.7%; p=0.013). It was significant after adjustment for age, sex, NYHA class, and LVEF. There was no association of overall HRQoL or domain scores with vaccination status. Younger age as a factor associated with vaccine avoidance in this population is consistent with data from the general population despite higher exposure to the severe course of the disease.